Relationship Between Information Technology and Multi-competence on Research Quality: Mediating Effect of Research Model Canvas - Astawa, I Ketut; Anak Agung, Putri Suardani; Putu Virgananta, Nugraha (Technium Social Sciences Journal, 2024)
In the rapidly evolving landscape of academic and industrial research, integrating Information Technology (IT) and Multi-Competence (MC) has become crucial for enhancing research quality (RQ). Despite growing recognition of their importance, the mechanisms through which IT and MC influence RQ, particularly through mediating tools like the Research Model Canvas (RM), remain underexplored. This study investigates the relationships between IT, MC, and RQ, with a specific focus on the mediating role of RM. The objective is to identify how IT and MC contribute to improving RQ and determine how much RM facilitates this process. A purposive sampling method was used to select 110 respondents, and data were collected through structured surveys and in-depth interviews. The data were analysed using Structural Equation Modeling with SmartPLS 4, a robust statistical tool for examining complex variable relationships. The findings reveal that while IT directly enhances RQ, it does not significantly affect RM, nor does RM mediate its effect on RQ. Conversely, MC significantly improves RM, which fully mediates its positive impact on RQ, highlighting the critical role of RM in translating competencies into research quality. The implications of this research suggest that organizations aiming to enhance research quality should focus on directly leveraging IT and utilizing strategic frameworks like RM to effectively channel multi-competence resources into improved research outcomes. This approach ensures that diverse skills meaningfully contribute to research success, particularly when mediated through structured models like the Research Model Canvas.